Colonization and Interaction of Bacteria Associated With Chinese Chives Affected by Ecological Compartments and Growth Conditions - Sun, Nan; Wang, Yuxin; Chen, Jianhua; Wang, Pingzhi; Song, Weitang; Ma, Peifang; Duan, Yabin; Jiao, Ziyuan; Li, Yixiao (Frontiers in Microbiology, 2022)
The effects of ecological compartment and growth conditions on bacterial communities in Chinese chives are unclear. Here, we aimed to elucidate the differences in bacterial a-diversity, ß-diversity, community structure, core species differences, interaction networks and predicted metabolic functions among bacterial communities in different ecological compartments (the phylloplane, leaf endosphere, stem endosphere, root endosphere and rhizosphere) in Chinese chives in an open field, a solar greenhouse, an arched shed and a hydroponic system. Sixty samples were collected from these five ecological compartments under four growth conditions, and we compared the bacterial profiles of these groups using 16S rRNA sequencing. We evaluated the differences in diversity and composition among bacterial communities in these ecological compartments, analysed the bacterial interaction patterns under the different growth conditions, and predicted the bacterial metabolic pathways in these ecological compartments and growth conditions. Proteobacteria occupied an absolutely dominant position in all ecological compartments. At the phylum level, the relative abundance of Proteobacteria decreased from the aboveground to belowground compartments. At the genus level, there were more genera in belowground than in aboveground compartments, and there were no significant differences among growth conditions. The genus $Pseudomonas$ showed a decreasing trend from top to bottom in the various ecological compartments within the plant. We believe that the genus $Pseudomonas$ mainly enters the plant through the phylloplane. In addition, interactions among bacteria were interrupted in the hydroponic system, and specific bacterial communities and interaction patterns in Chinese chives varied among growth conditions. Prediction of metabolic functions indicated that plant metabolic activity related to stress responses and induction of system resistance was greater in belowground ecological compartments.